2013
DOI: 10.3109/02713683.2012.753094
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Acoustic Microscopy for Mapping the Microelastic Properties of Human Corneal Tissue

Abstract: SAM is a novel tool for examining corneal tissue with a high spatial resolution, providing both histological and mechanical data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…In another study performed with a 761-MHz transducer, Beshtawi et al (2013) compared c at the lm-scale of human cross-linked corneas with controls and found a significant 5% increase in c for the treated specimens. The study did not assess a or Z.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In another study performed with a 761-MHz transducer, Beshtawi et al (2013) compared c at the lm-scale of human cross-linked corneas with controls and found a significant 5% increase in c for the treated specimens. The study did not assess a or Z.…”
Section: Discussionmentioning
confidence: 95%
“…These studies revealed significant variations in the acoustic properties, e.g., in cancerous tissue or atherosclerosis, indicating that structural changes of soft tissues are manifested in the mechanical properties of tissue at the micron level. Few studies have reported SAM measurements for ocular tissues (Beshtawi et al, 2013;Marmor et al, 1977). Beshtawi et al (2013) found a 5% increase of c of corneal tissue using SAM and Marmor et al (1977) found significant variations of acoustic properties of retinal layers.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, measuring them with microscopic resolution can provide invaluable information regarding the pathogenesis of these diseases. However, very few studies have reported SAM measurements for ocular tissues [4], [16], [17]. Beshtawi et al [17] found a 5 % increase of speed of sound of cross-linked corneal tissue compared to cryosectioned corneas using SAM.…”
Section: Introductionmentioning
confidence: 99%
“…However, very few studies have reported SAM measurements for ocular tissues [4], [16], [17]. Beshtawi et al [17] found a 5 % increase of speed of sound of cross-linked corneal tissue compared to cryosectioned corneas using SAM. Marmor et al [4] found significant variations of acoustic properties of retinal layers.…”
Section: Introductionmentioning
confidence: 99%